Ophthalmological involement and laboratory changes in patients with ANCA-associated vasculitis and polyarteritis nodosa (Ukrainian Journal of Ophthalmology, 2025)
Purpose. Aim of the study was to identify the frequencies and patterns of OI in patients with ANCA-associated vasculitis (AAV) and polyarteritis nodosa (PAN) and evaluate the laboratory changes depending on OI.Material and Methods. This work included retrospective study (112 patients with PAN and 80 patients with AAV) and prospective cohort study, which evaluated serum levels of endothelin-1 (ET-1) in 36 patients and 26 healthy сontrols. Results. OI at diagnosis in AAV occurred 4 times more often compared to PAN and consisted of conjunctivitis/episcleritis (16% AAV patients), optic neuropathy (5% PAN patients), orbital mass, uveitis, scleritis, epiphora or dry eyes. OI was more commonly detected in PR3-ANCA(+) vs PR3-ANCA(-) patients. The levels of ET-1 were elevated in patients without OI compared with control group and patients with OI, but ability of ET-1 to differentiate such patients was poor. Conclusion. The most common OI in patients with AAV was episcleritis. Optic neuropathy was the only manifestation of OI in patients with PAN. OI were more commonly detected in PR3-ANCA(+) vs PR3-ANCA(-) patients. The serum levels of ET-1 were significantly elevated in patients without OI compared with patients with OI and control group, but its diagnostic value was not approved in the ROC analysis.
Keywords: eye involvement; anti-neutrophil cytoplasmic antibody-associated vasculitis; granulomatosis with polyangiitis; eosinophilic granulomatosis with polyangiitis; microscopic polyangiitis; polyarteritis nodosa